Identification of circumstances in which heartwater has a major economic impact for the livestock industry in Southern Africa - Minjauw, B.; Perry, Brian D.; Randolph, Thomas F.; McDermott, John J.; Kruska, Russell L. (Slovak Academy of Sciences, 2000)
Heartwater, transmitted by Amblyomma spp., is considered one of the most important tick-borne diseases of cattle, goats and sheep in southern Africa, causing considerable losses through mortality and control costs. In support of a project developing a new inactivated vaccine, we have undertaken, an evaluation of the relative importance of heartwater in the major production systems in 9 countries of the SADC region. With the collaboration of Veterinary Departments, data on heartwater occurrence, control methods and production indices were collected and collated by livestock species and major livestock production system. Annual Reports of Veterinary Departments include only confirmed heartwater cases, probably only a very small proportion of the actual cases. This is mainly due to the difficulty of obtaining a definitive diagnosis, which requires examination of brain smears. Even though underestimated, heartwater was diagnosed in all production systems and in goats, sheep and cattle in all countries. Incidence and mortality are the most important parameters influencing economic impact. Control costs are important in some production systems and in these systems, it is difficult to estimate the proportion of control costs that should be allocated to different tick-borne diseases. This has tremendous impact on estimates of economic impact of heartwater. The estimated economic impact of heartwater in southern Africa varies by ecological, farm management and/or livestock policy circumstances. Highest economic losses due to heartwater occur when livestock are moved into a new area, either for restocking or for upgrading the existing indigenous breeds, and where there are significant fluctuations in the tick distribution and challenge. Some exotic species like Angora goats seems to be particularly susceptible. In contrast, indigenous livestock in the communal sector develop endemic stability. The identification of highest impact systems is an important first step in estimating potential economic benefits of vaccines under Development and provides information on the size of potential markets for new vaccines.